ANALISIS HUKUM PELANGGARAN TERHADAP DIGITALISASI CIPTAAN (Faculty of Law, University of Palembang, 2023)
Intellectual property rights are equivalent to intellectual property rights which are defined as protection of works created by human intellectual abilities in the fields of art, literature, science, aesthetics and technology. Copyright protection in Indonesia is currently one of the focuses of public attention, not only in the financial sector, law enforcement agencies must adapt to this development, especially related to the protection of intellectual property as an issue of violations in this digital development. The research method used is normative juridical, namely studying legal norms, examining all laws and regulations that are related to the legal issues being handled, with this it is known that the form of copyright regulation refers to Law Number 28 of 2014 concerning Copyright and Law Number 19 of 2016 concerning ITE, forms of illegal video streaming violations committed by actors in digitizing creations based on statutory regulations are duplicating, producing, distributing, displaying or exhibiting creations or making derivative works illegally so that illegal video streaming fulfills the element of violation Copyright in Chapter XXV Article 380 of the Criminal Code and Law Number 28 of 2014, is a criminal act and an unlawful act and therefore the perpetrator of the violation can be subject to the threat of criminal punishment, criminal responsibility is regulated in Law Number 28 of 2014 Articles 95, 105, 110-120 where demands crime is carried out as a last resort after mediation efforts fail Article 95 paragraph (4)